Streptococcus spp. from bulk-tank milk and milking machine teatcups on small ruminant farms, and factors potentially associated with their isolation. Issue 3 (4th August 2020) - Chatzopoulos, Dimitris C.; Lianou, Daphne T.; Michael, Charalambia K.; Gougoulis, Dimitris A.; Mavrogianni, Vasia S.; Vasileiou, Natalia G. C.; Katsafadou, Angeliki I.; Politis, Antonis P.; Kordalis, Nikos G.; Katsarou, Eleni I.; Ioannidi, Katerina S.; Petinaki, Efthimia; et al.
Abstract: The objectives of this work were (a) to determine the presence of streptococci in samples from small ruminant dairy farms (bulk-tank milk and, where possible, teatcup swabs), (b) to investigate the potential adverse effects of streptococci on milk quality and (c) to investigate the importance of some husbandry factors for the isolation of streptococci. Bulk-tank milk samples and teatcups swab samples were examined bacteriologically for the presence of streptococci. Somatic cell counting and milk composition measurements were also performed. The husbandry factors present in each farm were assessed for potential associations with the isolation of streptococci. Streptococci were isolated from milk samples from 31.4% of sheep and 17.4% of goat farms and from 4.8% of sheep and 5.9% of goat teatcups. Streptococci were isolated more frequently from the upper part than the lower part of teatcups: 5.0% vs. 1.9%. Most isolates (57.9%) were identified as Streptococcus uberis . Most isolates (68.4%) were slime-producing; slime-production was more frequent among isolates from teatcups (83.3%) than from bulk-tank milk (55.0%). Somatic cell counts and milk composition did not differ between farms in which streptococci were or were not isolated. Machine-milking was associated with the isolation of streptococci from bulk-tank milk samples. The initial stage of the milking period (first two months) was found to be associated with the isolation of streptococci from milking machine teatcups in sheep farms only.